Effect of Andrographis paniculata Leaf Crude Extract Against Edwardsiella tarda Bacteria and Histopathological Profile of the Liver of Osphronemus gouramy Juvenil - Giri Pratama; Arief Prajitno; Titik Dwi Sulistiyati (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research